Review article: moving towards common therapeutic goals in Crohn's disease and rheumatoid arthritis. Issue 8 (1st March 2017) - Allen, P. B.; Olivera, P.; Emery, P.; Moulin, D.; Jouzeau, J.‐Y.; Netter, P.; Danese, S.; Feagan, B.; Sandborn, W. J.; Peyrin‐Biroulet, L.
Summary: Background: Crohn's disease (CD) and rheumatoid arthritis are chronic, progressive and disabling conditions that frequently lead to structural tissue damage. Based on strategies originally developed for rheumatoid arthritis, the treatment goal for CD has recently moved from exclusively controlling symptoms to both clinical remission and complete mucosal healing (deep remission), with the final aim of preventing bowel damage and disability. Aim: To review the similarities and differences in treatment goals between CD and rheumatoid arthritis. Methods: This review examined manuscripts from 1982 to 2016 that discussed and/or proposed therapeutic goals with their supportive evidence in CD and rheumatoid arthritis. Results: Proposed therapeutic strategies to improve outcomes in both rheumatoid arthritis and CD include: (i) evaluation of musculoskeletal or organ damage and disability, (ii) tight control, (iii) treat‐to‐target, (iv) early intervention and (v) disease modification. In contrast to rheumatoid arthritis, there is a paucity of disease‐modification trials in CD. Conclusions: Novel therapeutic strategies in CD based on tight control of objective signs of inflammation are expected to change disease course and patients' lives by halting progression or, ideally, preventing the occurrence of bowel damage. Most of these strategies require validation in prospective studies, whereas several disease‐modification trials have addressed these issues in rheumatoid arthritis over the last decade. The recent approval of new drugs in CD such as vedolizumab and ustekinumab should facilitate initiation of disease‐modification trials in CD in the near future.